Competition and niche separation in a high altitude herbivore community in Ethiopia - Dunbar, RIM (Wiley, 1978)
Seven species of herbivores (a primate, four ungulates and two domesticated species) which formed a semi-natural community were studied in a montane heath habitat in northern Ethiopia. All species were found to have increased in numbers over a 3-year period, so that no species could be said to be suffering from ecological competition in the strict sense. Several of the species were in the process of re-establishing themselves following periods of absence or reduced density, so that competition at present is more likely to be incipient rather than actual. Analyses of each species' gross dietary profile and its use of the habitat suggested a clear differentiation into two groups, graminivores and true herbivores, with ecological overlap between species in the same category being minimized by differential habitat use. The data were used to test the prediction that greater levels of dietary overlap would be possible in the more diverse sections of the habitat: the results were equivocal, possibly due to the low densities of many of the species. Some evidence was found to support the hypothesis that there would be a reduction in dietary overlap during the dry season when food resources were in short supply. However, the extent to which this actually occurred seemed to depend on the levels of overlap when food was plentiful: the reverse might in fact be the case for pairs of species whose diets normally overlapped little, for these often seemed able to tolerate greater overlap in diet during critical periods.